Experience of the psychiatric and psychotherapy services of an infectious hospital in the context of the COVID-19 pandemic - G. A. Prokopovich; T. V. Vladykina; M. S. Sivashova; O. N. Zueva (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева, 2021)
The article reflects the results of the work of the psychiatric and psychotherapy services of the Hospital for war veterans converted into an infectious hospital in the context of the new coronavirus infection (COVID-19) pandemic. The aim of our study was to determine the frequency and nature of mental disorders in patients treated in hospital for a new coronavirus infection (COVID-19) between April and June 2020. The case histories of patients who received psychotherapy or psychiatric care in addition to the treatment of the underlying disease were studied retrospectively. The study included 557 patients, 266 men, 291 women, the average age was 62.36+18.65 years. The work used clinical and psychological methods using the international classification of diseases 10 revision (ICD-10), the diagnosis of a new coronavirus infection (COVID — 19) was carried out in accordance with the Temporary guidelines of the Ministry of health of the Russian Federation. As a result of data evaluation, it was revealed that the proportion of patients requiring consultation or treatment by a psychiatrist or psychotherapist was 557 (7,10%) patients of the total number of hospital admissions, of which emergency psychiatric care was indicated in 58 (10,41%) of cases. The transition of the hospital to an infectious diseases hospital mode has set new challenges for the psychiatric and psychotherapy service, which required organizational measures, therapeutic issues and confirmed the need for participation of mental health specialists in providing full-fledged medical care in the treatment of somatic disorders.